Aplikasi Kitab Al Hikam di Pondok Pesantren Bi Ba‘a Fadlrah Turen Kabupaten Malang - Jawa Timur - Samidi Khalim (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
This is the study of al-Hikam, the book written by Ibn Athaillah, whichis taught in the Pesantren Biharu Bahri Asalai Fadhailir Rahmah in Turen,Malang, East Java. The research used content analysis and mysticism approach.In the pesantren the teachings of the Hikam is not purely taught as knowledge butalso applied in daily activities. Nevertheless, not all teachings of the book could be easily implemented in the real life but four major teachings are given a great consideration: al Muhasabah, al-Yaqin, Husnudhan, and al-Tawakkal.